Peru : Staff Report for the 2000 Article IV Consultation and Request for a Stand-By Arrangement. (IMF Staff Country Reports; Country Report ;, 2001)
Peru's economic performance was influenced by adverse external shocks and political uncertainty. Executive Directors welcomed the interim government's economic objective to secure macroeconomic stability in the transition to a new government, while making progress on structural reforms. They stressed the need to strengthen the soundness of the banking system, and the monetary and fiscal policies. Directors welcomed the transparency of government operations, the tax administration, the quality of labor market data, the flexible exchange rate system, and an open trade and payments regime.